2020
DOI: 10.1021/acsomega.0c00285
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Layered Nanomaterial-Based Molecular Pattering on Polymer Surface Biomimetic Impedimetric Sensing of a Bliss Molecule, Anandamide Neurotransmitter

Abstract: In this endeavor, a novel electrochemical biosensor was designed using multiwall carbon nanotubes (MWCNTs)- and nickel nanoparticles (NiNPs)-embedded anandamide (AEA) imprinted polymer. The NiNPs so synthesized were mortared with MWCNTs and molecularly imprinted polymer (MIP), which enhanced sensitivity and selectivity of the developed sensor, respectively. The characterization methods of AEA-based MIP included X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…The MAPA monomer, with a similar molecular structure to DA through its various binding sites presented by phenylalanine, offers greater sensitivity with a low detection of limit for the MIP PGE sensor for DA detection compared to the other imprinted electrode sensors that are mentioned in the literature [36,37]. Nevertheless, many related imprinted polymer electrode sensors demonstrating parallel or better limits of detection have been reported (Table 3).…”
Section: Da Determination In a Real Biological Samplementioning
confidence: 99%
“…The MAPA monomer, with a similar molecular structure to DA through its various binding sites presented by phenylalanine, offers greater sensitivity with a low detection of limit for the MIP PGE sensor for DA detection compared to the other imprinted electrode sensors that are mentioned in the literature [36,37]. Nevertheless, many related imprinted polymer electrode sensors demonstrating parallel or better limits of detection have been reported (Table 3).…”
Section: Da Determination In a Real Biological Samplementioning
confidence: 99%
“…The increased level of blood sugar has a lasting impact on the patient’s body, with some of these effects being organ failure (eyes, blood vessels, nerves, kidneys, and heart) or dysfunction. The latest reports generated by the International Federation of Clinical Chemistry and Laboratory Medicine (IFCC) show that about 415 million people are affected by diabetes globally, and 47% of the population are not aware of their condition. Globally, it was observed that the number of adults suffering from diabetes increased from 198 (1980) to 422 (2014) million. The global prevalence increased from 4.7 to 8.5% in 1980.…”
Section: Introductionmentioning
confidence: 99%
“…They provide higher sensitivity, specificity, and thermal stability. MIP integrated biosensing platforms are stable at higher temperatures and pressure. In this work, fructosyl amino acid oxidase was used as a template and HbA1c as an analyte. The concentration of HbA1c is determined with further experimentation, and different conditions were examined on the biosensor surface to check and evaluate the activity, stability, and other parameters of the designed nanobiosensor.…”
Section: Introductionmentioning
confidence: 99%
“…Classical techniques, such as suspended droplet-based liquid–liquid extraction and supported liquid extraction, require incubation, washing, and separation during sample processing. These techniques to functionally quantify analytes, however, are expensive and time-consuming, primarily because of the complexity of preliminary sample preparation techniques [ 9 , 10 ]. To broadly enable the analysis, the developed sensor for drug testing should be simple, rapid, and cost-effective.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decades, nanotechnology has been introduced to analytical methods and sensing technologies to improve the sensitivities of platforms. In this direction, metallic nanomaterials such as iron [ 22 ], zinc [ 23 , 24 ], nickel [ 9 , 25 ], and tin [ 18 , 26 ] have been suggested as promising matrices for the sensing application. Tin nanoparticles (SnNPs) are especially promising materials that exhibit unique physicochemical properties to promote transduction processes in electrochemical sensors.…”
Section: Introductionmentioning
confidence: 99%